Genetic Counseling in the Follow-up of Breast Cancer patients; Conversion of a Luminal Tumor to TNBC - Ahmadi, Hamid; Hosseinpour, Reza; Jahanbin, Behnaz; Majidzadeh-A, Keivan; Azmoudeh-Ardalan, Farid (Archives of Breast Cancer, 2020)
Background: Triple-negative subtype does not have any of the receptors that are commonly found in breast cancer. Patients suffering from Triple-negative breast cancer are at risk of early metastasis and BRCA mutation. The conversion of the receptors during the metastatic progression or local recurrence of breast cancer is a well-known topic that affects the therapeutic measures and outcome. Confirmation of immunohistochemistry is essential in these conditions, but genetic evaluation is controversial. Case presentation: A woman suffering from primary luminal breast cancer presented with femoral bone metastasis in the follow-up after two years. Bone metastasis was compatible with the triple-negative subtype. This case was discussed at the weekly breast multidisciplinary team session of the Department of Breast Surgery, Tehran University of Medical Sciences. Question: Does the patient need genetics counseling in a conversion setting? And does the new specimen need CISH/FISH techniques to confirm TNBC tumors? Conclusion: There are no strong guidelines to recommend genetic counseling and BRCA testing for patients with breast cancer biomarkers conversion. Re-assessing the specimen for ER, PR, and HER-2 is necessary for this setting.